Economic history of Orissa in the 19th century - Das, Purna Chandra (New Delhi Commonwealth, 2024)
This book presents an interesting and detailed analysis of the economic history of the people of Orissa. Since the British occupation in 1803 which is based on the original source materials.
Keywords: Finance and Economy; Economy of Orissa; Economic History of Orissa